2021
DOI: 10.1103/physrevb.104.144510
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting and structural properties of the type-I superconductor PdTe2 under high pressure

Abstract: The transition metal dichalcogenide PdTe 2 has attractive features based on its classification as a type-II Dirac semimetal and the occurrence of type-I superconductivity, providing a platform for discussion of a topological superconductor. Our recent work revealed that type-I superconductivity persists up to pressures of ∼2.5 GPa and the superconducting transition temperature T c reaches a maximum at around 1 GPa, which is inconsistent with the theoretical prediction. To understand its nonmonotonic variation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Combing the superconductivity and the topological nontrivial band structure, PdTe 2 is considered as a topological superconductor candidate. Pressure experiments showed that the superconducting transition temperature decreases from 1.8 K at 1 GPa to 0.82 K at 5.5 GPa [25,26]. First-principle calculations predicted a new pair of type-I Dirac cone emerges at 4.7 GPa and the coexistence of type-I and type-II Dirac cones under proper pressure (4.7 GPa-6.1 GPa) [27].…”
Section: Introductionmentioning
confidence: 98%
“…Combing the superconductivity and the topological nontrivial band structure, PdTe 2 is considered as a topological superconductor candidate. Pressure experiments showed that the superconducting transition temperature decreases from 1.8 K at 1 GPa to 0.82 K at 5.5 GPa [25,26]. First-principle calculations predicted a new pair of type-I Dirac cone emerges at 4.7 GPa and the coexistence of type-I and type-II Dirac cones under proper pressure (4.7 GPa-6.1 GPa) [27].…”
Section: Introductionmentioning
confidence: 98%
“…[22,38] The application of pressure can effectively tune the crystal structures and the corresponding electronic states in a valid and systematic fashion, and its related studies on MX 2 , indeed, have given rise to many novel physical phenomena. [23,[39][40][41][42][43][44] To date, the high-pressure properties of ZrTe 2 have not been well explored. Here, we systematically explore the structure and electronic properties of topological TMDC ZrTe 2 single crystal under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, evidence for bulk type-I superconductivity was attained through heat capacity measurements by demonstrating the presence of latent heat [12]. Measurements under hydrostatic pressure show that superconductivity is still present at 5.5 GPa [26] and remains of the first kind at least till 2.5 GPa [27].…”
Section: Introductionmentioning
confidence: 99%